Antimicrobial Analysis of an Antiseptic Made from Ethanol Crude Extracts of P. granatum and E. uniflora in Wistar Rats against Staphylococcus aureus and Staphylococcus epidermidis - Thaís Honório Lins Bernardo; Regina Célia Sales Santos Veríssimo; Valter Alvino; Maria Gabriella Silva Araujo; Raíssa Fernanda Evangelista Pires dos Santos; Max Denisson Maurício Viana; Maria Lysete de Assis Bastos; Magna Suzana Alexandre-Moreira; João Xavier de Araújo-Júnior (The Scientific World Journal)
Introduction. Surgical site infection remains a challenge for hospital infection control, especially when it relates to skin antisepsis in the surgical site. Objective. To analyze the antimicrobial activity in vivo of an antiseptic from ethanol crude extracts of P. granatum and E. uniflora against Gram-positive and Gram-negative bacteria. Methods. Agar drilling and minimal inhibitory tests were conducted for in vitro evaluation. In the in vivo bioassay were used Wistar rats and Staphylococcus aureus (ATCC 25923) and Staphylococcus epidermidis (ATCC 14990). Statistical analysis was performed through variance analysis and Scott-Knott cluster test at 5% probability and significance level. Results. In the in vitro, ethanolic extracts of Punica granatum and Eugenia uniflora and their combination showed the best antimicrobial potential against S. epidermidis and S. aureus. In the in vivo bioassay against S. epidermidis, there was no statistically significant difference between the tested product and the patterns used after five minutes of applying the product. Conclusion. The results indicate that the originated product is an antiseptic alternative source against S. epidermidis compared to chlorhexidine gluconate. It is suggested that further researches are to be conducted in different concentrations of the test product, evaluating its effectiveness and operational costs.